Strain transfer across grain boundaries in MoS2 monolayers grown by chemical vapor deposition. (16th April 2018) - Niehues, Iris; Blob, Anna; Stiehm, Torsten; Schmidt, Robert; Jadriško, Valentino; Radatović, Borna; Čapeta, Davor; Kralj, Marko; de Vasconcellos, Steffen Michaelis; Bratschitsch, Rudolf
Abstract: Monolayers of transition metal dichalcogenides (TMDC) mechanically exfoliated from bulk crystals have exceptional mechanical and optical properties. They are extremely flexible, sustaining mechanical strain of about 10% without breaking. Their optical properties dramatically change with applied strain. However, the fabrication of a large number of mechanical devices is tedious due to the micromechanical exfoliation process. Alternatively, monolayers can be grown by chemical vapor deposition (CVD) on the wafer scale, with the drawback of cracks and grain boundaries in the material. Therefore, it is important to investigate the mechanical properties of CVD-grown material and its potential as a material for mass production of nanomechanical devices. Here, we measure the optical absorption of CVD-grown MoS2 monolayers with applied uniaxial tensile strain. We derive a strain-dependent shift for the A exciton of  −42 meV/%. This value is identical to MoS2 monolayers, which are mechanically exfoliated from natural molybdenite crystals. Using angle-resolved second-harmonic generation spectroscopy, we find that the applied uniaxial tensile strain is fully transferred across grain boundaries of the CVD-grown monolayer. Our work demonstrates that large-area artificially grown MoS2 monolayers are promising for mass-produced nanomechanical devices.